Development of fibre interferometer sensors based on double cladding fibre for multi-parameter sensing - Siti Musliha Aishah Musa, 1991-, author 524648; Asrul Izam Azmi, supervisor 185626; Raja Kamarulzaman Raja Ibrahim, supervisor 297480; Muhammad Yusof Mohd. Noor, supervisor 306420; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2021)
Thesis (Doktor Falsafah (Fizik)) - Universiti Teknologi Malaysia, 2021